Effect of Some Packing Materials on Oxidative Stability of Fats in Date Biscuits - Rania, I.M. Almoselhy (Food Technology Research Journal)
Functional biscuits are considered energetic dietary supplements for children suffering from malnutrition and micronutrient deficiency. Biscuits stuffed with date paste and fortified with minerals and vitamins have a considerable fat content where lipid oxidation processes may occur with improper packing which affects the quality and safety of biscuits leading to their contamination with pathogenic microorganisms and toxic chemicals. Therefore, the current study aimed to investigate the oxidative stability of fats in date biscuits and their shelf life under different types of packing materials ranging from sealed translucent polypropylene (PP), and sealed metalized polypropylene (MPP), compared with the control unsealed translucent polyethylene (PE) bags. Physicochemical, microbiological, storage and sensory evaluations for biscuits samples under the different packing materials along with the chemical migration test for the packing materials were carried out. Results showed significant differences (P < 0.05) among samples with increasing acidity, peroxide value, diene, and triene, whereas, the iodine value and oxidative stability decreased with storage periods. Fatty acid composition showed slight changes with a decrease in unsaturated fatty acids (ΣUSFA) due to the lipid oxidation processes with the emergence of trans-fatty acids after 90 days of storage with the emergence of microbiological activity expressed in a considerable increase in the aerobic plate count (APC) and total combined yeasts and molds count (TYMC) in the control sample (PE) compared with PP and MPP with the superiority of MPP as the best packing material for maintaining the best quality and safety of biscuits with lowest lipid oxidation and highest shelf life.